EU - kako naprej? Model asimetričnega odločanja kot sredstvo za urejanje in upravljanje različnosti v Evropi - Žagar, Mitja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2005)
Discussions on the future of European integration processes open up a series of current issues which are also relevant from the viewpoint of managing of ethnic, cultural and all other diversities in Europe. The article mostly focuses on questions of the future institutional development of the EU in the light of problems regarding the ratification of the Constitution Treaty for Europe. Various viewpoints and coordination of different interests between member states, including standpoints regarding institutional and other EU reforms, are dealt with, as are possible solutions, mechanisms and models for coordination of interests. Special attention is dedicated to the model of asymmetric decision making. This model could serve as a possible answer to reflections on Europe of different circles and paces, and above all as a modeland mechanism for the expressing of different diversities. Although such a model was often linked to reflections on asymmetric federalism - also in discussions on the federalization of the EU - it could also be used in case if this integration did not decide upon further development towards federalism.
Keywords: European Union; Evropska unija; integracijski procesi; federacija; odločanje; modeli odločanja